2021
DOI: 10.3390/medicina57090878
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Clinical Prognosis of Critically Ill Patients with COVID-19 Admitted to Intensive Care Units: A Nationwide Saudi Study

Abstract: Backgroundand Objectives: COVID-19 is a novel infectious disease caused by a single-stranded RNA coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We aimed to conduct a nationwide multicenter study to determine the characteristics and the clinical prognostic outcome of critically ill COVID-19 patients admitted to intensive care units (ICUs). Materials and Methods: This is a nationwide cohort retrospective study conducted in twenty Saudi hospitals. Results: An analysis of 1470 cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 38 publications
(45 reference statements)
3
12
0
2
Order By: Relevance
“…In line with our findings, the mortality rate among the recipients of mechanical ventilation was high at 82.7%. 15 A large study by Alhumaid et al 30 reported clinical features and prognostic factors of 1014 COVID-19 patients from six hospitals in Al-Ahsa between 1 March 2020 and 30 July 2020, a 2-month overlap with our study and found the same common comorbidities as in our study. However, Alhumaid et al did not report mortality rates among patients on mechanical ventilation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In line with our findings, the mortality rate among the recipients of mechanical ventilation was high at 82.7%. 15 A large study by Alhumaid et al 30 reported clinical features and prognostic factors of 1014 COVID-19 patients from six hospitals in Al-Ahsa between 1 March 2020 and 30 July 2020, a 2-month overlap with our study and found the same common comorbidities as in our study. However, Alhumaid et al did not report mortality rates among patients on mechanical ventilation.…”
Section: Discussionsupporting
confidence: 83%
“… 14 Several nationwide studies from Saudi Arabia have identified common comorbidities in intensive care patients (hypertension, diabetes, ischemic heart disease). 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…14 Several retrospective case-control studies and randomized trials evaluated the role of tocilizumab in reducing the mortality of severe COVID-19 and had conflicting results. [7][8][9][10][11][15][16][17][18][19][20] However, SOT recipients were not included in these studies except for one study, which only included nine cases (6%). 21 The largest cohort of COVID 19 transplant patients who received IL-6 blockers included 80 cases in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…3 The same pattern of COVID-19 severity was reported in Saudi Arabia with various clinical presentations including mild, moderate, and critical cases; in addition to asymptomatic cases. [4][5][6][7][8] Previous studies showed that COVID-19 disease is associated with an increase in plasma concentrations of cytokines and inflammatory markers including elevation of ferritin, lactate dehydrogenase (LDH), D-dimer, and C-reactive protein (CRP). [9][10][11] Additionally, lung tissue histopathology examination of COVID-19 deceased patients showed inflammatory cellular infiltration, proteinaceous exudate, and evidence of extensive alveolar edema.…”
Section: Introductionmentioning
confidence: 99%
“…As the COVID-19 pandemic continues to cause new cases worldwide, the epidemiology of SARS-CoV-2 infection is evolving with the emergence of variant strains of concern, in addition to the reporting of an increasing number of cases among children ( 1 , 2 ). Both adults and children with comorbidities infected with COVID-19 are at risk to develop severe pneumonia requiring hospitalization ( 3 , 4 ). Although they are rare, children with genetic diseases infected with SAS-CoV-2 infection were more likely to be hospitalized and develop severe illness and intensive care unit admission ( 5 ).…”
Section: Introductionmentioning
confidence: 99%